PELATIHAN ANALISIS BIAYA PRODUKSI UMKM DI DESA WRINGINSONGO - Ahmad Jarnuzi; Annisa Fitriana; Apit Miharso; Bakhrudin; Fathimatus Zahro Fazda Oktavia (Publisher UPT P2M Politeknik Negeri Malang, 2021)
This PPM is held to reformulate the determination of the basic water tariff on the clean water management unit that is part of BUMDes Desa Wringinsongo, a method used with a qualitative approach where the team identifies the problem of the partner, then determines the objectives, reformulates and implements the partner. PPM results recommend the use of water account applications as well as admin fee of Rp.1000